Advancement of life and death education research: recommending implementation of the Life + Death Education Framework for teaching and research purposes - Huy P. Phan; Huy P. Phan; Bing Hiong Ngu; Chao-Sheng Hsu; Si-Chi Chen (Frontiers Media S.A., 2024)
Life and death education is a distinct field of study that has potential practicality and life relevance for us to consider. For example, one notable inquiry pertaining to life education teaching entails appreciation and theoretical understanding of quality life functioning (e.g., a person's desire to attain spiritual wisdom vs. a person's desire to attain immense financial wealth). Our research undertakings recently involved the development of a blueprint or framework, which we termed as the 'Life + Death Education Framework'. This framework is intended to provide relevant information that may serve to assist educators, stakeholders, caregivers, etc. with their teaching practices of life and death education. We premise that to date, there is no clear consensus or agreement among educators as to what one is expected (e.g., specific learning outcome) to teach to students who wish to study and learn about life and death education (e.g., do we introduce to students the metaphysical lens about death?). Moreover, from our point of view, the Life + Death Education Framework may yield insightful guidelines and life-related benefits, such as the heightening of a person's well-being and/or his or her daily life functioning. As such, then, the focus of the present theoretical-conceptual article is for us to provide an in-depth narrative of the Life + Death Education Framework and how this framework, or potential universal blueprint, could help introduce and clarify our proposition of a life functioning-related concept known as 'self well-being'. Self well-being, for us, is an alternative nomenclature that may be used in place of subjective well-being.